Factors Influencing the Selection of Healthy and Unhealthy Diet Behavior in Adolescent Girls in Bandar Lampung - Dian Isti Angraini; Asiah Nurul Izzah; Khairun Nisa; Reni Zuraida (International Journal of Advanced Health Science and Technology, 2023)
Adolescence is a period of a transitional development from children to adult women who are generally 10-21 years old. Adolescents have significant physical, psychosocial, and cognitive changes that can affect adolescent dietary behavior. The purpose of this study was to determine the effect of affecting factors on unhealthy dietary behavior in adolescent girls. This research is an analytic observational study, with a cross-sectional design approach using primary data, which was conducted from April to June 2022. The sample is 135 adolescent girls aged 15-21 years old taken using multistage random sampling who met the inclusion and exclusion criteria. The data was obtained by filling out the questionnaire and analyzed by using the chi-square test. The results showed that 56.3% of respondents had unhealthy dietary behavior. The results of the bivariate analysis showed that nutritional status (p = 0.000; PR = 2.072) and body image (p = 0.000; PR = 0.559) influenced unhealthy dietary behavior. Meanwhile, knowledge (p=0,227), age (p=0,158), pocket money (p=0,452), and peers (p = 0.120) did not influence unhealthy dietary behavior. It can be concluded that there is an influence of nutritional status and body image factors on unhealthy diet behavior. Based on the research results, adolescent girls must have a healthy diet according to balanced nutrition guidelines in achieving normal nutritional status and a good body image.